Execution Time Limitation of Interrupt Handlers in a Java Operating System - Felser, Meik; Golm, Michael; Wawersich, Christian; Kleinöder, Jürgen (Tenth ACM SIGOPS European Workshop, 2002)
Device drivers are a very critical part of every operating system. They often contain code that is executed in interrupt handlers. During the execution of interrupt handlers, the processing of some other interrupts is usually disabled. Thus errors in that code can compromise the whole system.This paper describes an approach to ensure that an interrupt handler is not allowed to use more than a specified amount of time. Our approach is based on a Java operating system and consists of a combination of verification at compilation time and run-time checks.
UnivIS-Import:2015-04-16:Pub.2002.tech.IMMD.IMMD4.execut
Keywords: JX; verifier; driver